2002
DOI: 10.1136/gut.50.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Crohn's disease with recombinant human interleukin 10 induces the proinflammatory cytokine interferon gamma

Abstract: Background: Interleukin 10 (IL-10) exerts anti-inflammatory actions by counteracting many biological effects of interferon γ (IFN-γ). Aims: To investigate this in humans, we studied the effects of human recombinant IL-10 administration on IFN-γ production by patient leucocytes. Furthermore, we assessed the IFN-γ inducible molecule neopterin and nitrite/nitrate serum levels, which are indicative of endogenous nitric oxide formation. Methods: As part of two placebo controlled double blind studies, we analysed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
160
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(172 citation statements)
references
References 23 publications
12
160
0
Order By: Relevance
“…41 Despite high levels of IL-10 protein expression in the lungs of mice receiving AAV5.Cb-mIL10, blood levels of proinflammatory cytokines and IL-10 from mice receiving AAV5.Cb-mIL10 were not significantly different from those measured in PBS-treated mice. This finding supports a localized IL-10 effect, an important safety feature because IL-10 leakage into the circulation could mediate systemic immunosuppression or even become immunostimulatory at high 45 rIL-10 administered systemically was previously found to attenuate both local and systemic effects. 19 There were several limitations in this study.…”
Section: Aav5cb-mil10 Mediates Il-10 Protein Expression In the Alveolisupporting
confidence: 83%
“…41 Despite high levels of IL-10 protein expression in the lungs of mice receiving AAV5.Cb-mIL10, blood levels of proinflammatory cytokines and IL-10 from mice receiving AAV5.Cb-mIL10 were not significantly different from those measured in PBS-treated mice. This finding supports a localized IL-10 effect, an important safety feature because IL-10 leakage into the circulation could mediate systemic immunosuppression or even become immunostimulatory at high 45 rIL-10 administered systemically was previously found to attenuate both local and systemic effects. 19 There were several limitations in this study.…”
Section: Aav5cb-mil10 Mediates Il-10 Protein Expression In the Alveolisupporting
confidence: 83%
“…In fact, the results compare favourably with other therapeutic strategies reported in mice with TNBS colitis; for example, IL-18 binding protein (42% fall in histological score) 26 and the chemokine receptor antagonist Met-RANTES (57% fall in histological score). 34 We have recently shown that subcutaneous administration of high-dose rIL-10 may have pro-inflammatory effects via induction of IFN-g. 15 No evidence of this was detected after AdvmuIL-10 therapy, since spleen cell production of IFN-g and TNF-a was not altered, and serum levels of IL-6 were decreased. This discrepancy may be explained by differences in the systemic IL-10 levels achieved and changes in the balance of its immunoregulatory and pro-inflammatory effects.…”
Section: Il-10 Gene Therapy Prevents Tnbs-induced Colitis J Lindsay Ementioning
confidence: 98%
“…Explanations for this lack of efficacy include the short half-life of rIL-10, 14 local delivery of insufficient amounts of rIL-10 to inhibit mucosal Th1 responses and the side effects associated with high-dose rIL-10. 15 Sustained IL-10 delivery may prove more effective than daily systemic injections. Indeed, daily intra-gastric administration of IL-10-secreting Lactococcus lactis caused a 50% reduction in disease severity in mice with dextran sulphate sodium induced colitis and prevented the onset of colitis in IL-10 À/À mice.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, although low doses of immunomodulant cytokines, such as rIL-10 in Crohn's disease, are relatively safe they are barely effective, whereas higher doses are associated with severe systemic side effects. 24, 25 An attractive . Animals injected intrarectally with DNBS were then randomly divided (n ¼ 8 per group) to receive by oral gavage either BHI vehicle (b), E. coli BM2710/ pGB2Oinv-hly carrying plasmid pC1OTGF-b1 (c), E. coli BM2710/pGB2 carrying plasmid pC1OTGF-b1 (d), E. coli BM2710/pGB2Oinv-hly carrying plasmid pC1 (e).…”
Section: Discussionmentioning
confidence: 99%